The anthelmintic activity of the white wormwood (Artemisia herba Alba) against Haemonchus contortus in beef cattle - Annamore Hoshiki; Washaya Soul; Nyamushamba Godfrey Bernard (Scientific Reports)
Abstract The objective of the study was to determine the efficacy of white wormwood on helminthes in beef cattle production. Water extracts of white wormwood of different levels of phytotoxicity were used to treat female adult H. contortus over 8 h under controlled laboratory conditions. The experiment was designed in a completely randomized design with six treatments replicated three times. Treatments 3–6 showed a reduction in worm motility over time (P < 0.05) while it did not change much for T1 and T2 (P < 0.05). Even after 8 h of incubation, more than 50% of the worms were still active in T1, T2 and T3. Meaningful reductions in activity were observed in T4 from 6 to 8 h, T5 form 4–8 h and T6 form 2–6 h. The highest mortality was observed in T4, T5 and T6, 8 h after incubation, however only T6 totally killed all worms 6 h after incubation. Treatments 4 and 5 only achieved 80 and 82% mortality respectively, 8 h post incubation. It is therefore concluded that wormwood aqueous extracts at 5 mg/mL and 10 mg/mL have the capability to immobilize, inactivate and kill mature H. contortus worms from beef cattle.